Development of web database for Malaysian alzheimer’s disease to Malaysian Research and Education Network (MyREN) / Ernny Ermati Mohd Sayuti - Mohd Sayuti, Ernny Ermati (2009)
Nowadays, it is important to have a responsive environment for retrieving data or information as it is a key component of the information system infrastructure of modern research projects. Due to the rapid growth of the global internet, researchers are demanding an improvement of traditional techniques for data storage in order to get desired information in a convenient fashion and at a higher speed. This project develops a web database in order to facilitate the researchers among the Malaysian Research and Education Network (MyREN) members to get the required information about Alzheimer's disease (AD). It helps the researchers to get the comprehensive information about the disease such as the DNA of patients along with their age and gender. The database is developed using MySQL and Hypertext Pre-processor (PHP). The Apache web server is used to display the information on the web browser. This system provides the facility to acquire AD information by features of interest for example age, sex, etc. Security is affordable by restricting access only to MyREN members. This web database provides a user friendly environment for ease of data access and a significant enhancement in data retrieval rate.